(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Nanostructured composites of the aluminum 7075 alloy and carbon-coated silver nanoparticles were synthetized by the mechanical milling technique using a high-energy mill SPEX 8000M; the powders generated were compacted, sintered and hot-extruded to produce 1 cm-diameter bars. The composites were then subjected to a wear test using a pin-on-disc device to validate the hypothesis that second phase-ductile nanometric particles homogenously distributed throughout the metal-matrix improve the wear resistance of the material. It was found that silver nanoparticles prevent the wear of the material by acting as an obstacle to dislocations movement during the plastic deformation of the contact surface, as well as a solid lubricant when these are separated from the metal-matrix.